EDUCATIONAL TECHNOLOGY - CONCEPTS AND IDENTIFICATION OF VOCABULARY IN THE DOMAIN - Binh, Lam Thi Hoa (VNU Journal of Foreign Studies, 2022)
The term educational technology (ET) has been mentioned in recent decades, but its concepts are many and keep changing over time. Pedagogic improvements to meet the needs of theoretical and practical knowledge in new professions and the ever-evolving technology of information and computer have made educational technology incredibly dynamic. On analyzing a number of notable concepts of educational technology having been used in Vietnam and in the world, the article specifies the widely accepted definition of educational technology in the 21st century, clarifies its typical features as a foundation to identify the scope of specialized vocabulary which can be used to compile handbooks and dictionaries to fill the gap of ET specialized lexicography in Vietnam.